Hydrodynamic microelectrode voltammetry - Rees, N; Compton, R (2008)
This review provides a detailed overview of the progress made in the last 25 years in the field of hydrodynamic microelectrodes (HMEs) with particular application to the study of electrochemical kinetics. A survey is made of the various types of HMEs that have been reported in the literature, with summaries of theoretical and experimental details along with the results published by each methodology. Conclusions are drawn regarding the comparative advantages and disadvantages of these techniques, and the channel and microject electrodes found to be preferred. © 2008 MAIK Nauka.